"He Wanted Everybody to Succeed": Black Males, Relational Trust, and School Counseling. Issue 1 (January 2021) - Brooms, Derrick R.
Based on qualitative interviews with 20 college-aged Black males who graduated from one single-sex public charter school, this study investigated how students made meaning from their secondary school experiences and college preparation. Using relational trust as the theoretical framework, I looked specifically at the students' perceptions and relationships with their school counselor. Findings revealed that the school counselor's investment in students helped them see and envision their possibilities, increased their access to critical postsecondary information and opportunities, and enhanced their motivations and aspirations toward college success. This article discusses recommendations for future research and practical suggestions for school counselors.